ANALYSIS OF DERIVATIONAL AFFIXES OF FUADI’S FIVE TOWERS NOVEL AND ITS CONTRIBUTION FOR GRAMMAR MEANING DISCOURSE - Sukma Nur Andini; Leni Pratiwi (Universitas PGRI Semarang, 2013)
Morphological analysis is the main areas in studying vocabulary. The objective of the research are: 1). To find out the derivational affixes found in The Land of Five Towers Novel. 2). To find out the contribution of derivational affixes from The Land of Towers a Novel. The Land of Five Towers Novel by A. Fuadi is a novel inspired by a true story from the author, that is Ahmad Fuadi. Having seeing such phenomenon, the writer found that mastering English is not easy if the students are lack of vocabulary. This research aimed at finding out the derivational affixes in The Land of Five Towers Novel by A. Fuadi. This research is descriptive qualitative research where researcher tries to find out the derivational affix and the roots from the words in The Land of Five Towers Novel without using statistical calculation. The result of analyzing data were gained the derivational affixes that found in The Land of Five Towers Novel by A. Fuadi are en-, in-, un-, a-, non-, re-, im- as prefixes, while the suffixes are –ly, -able, -er, -al, -ous, -ate, -cy, -y, -ee , –tion, -ion, -ize , -ship, -ment, -ism, -ist, -en, -ful, -age, -tic, -ish, -ary, -cent, -ive, -ance, -less, -ence, -ity, -ant, -or, -ness, -ure, -fy. In The Land of Five Towers Novel by A. Fuadi, the roots from the words that has been classified based on the part of speech are 199 (adjective), 188 (noun), 266 (verb). Thus, the writer suggests that to improve their mastery of vocabulary, the readers should be apply the derivational affixes by breaking the word into its elements that are root and affixes because one word can be built from more than one morpheme. By knowing the roots, the readers can build the word by easily themselves.